Rendimiento laboral y su efecto en el desempeño eficiente de las actividades empresariales desarrolladas por la secretaria ejecutiva en el decanato de la facultad de ciencias jurídicas, sociales y de la educación de la Universidad Técnica de Babahoyo. - Poveda Vargas, Milenia Arelys (2021)
This case study was conducted at the Technical University of Babahoyo, specifically in the dean's office of the Faculty of Sciences, Law, Social and Education, whose main objective is to analyze how the aspects that involve low job performance directly affect the management of business activities developed by the executive secretary, so that the results obtained by means of the techniques applied in this research will serve as a focus for the solutions that will contribute to the problem in question, so that the reader of this research will obtain more knowledge about the negative aspects that affect the promotion of labor inefficiency and also positive aspects that contribute to the success and recognition of an institution of higher education or a company. In response to the problem, a public university was chosen as a method of research on the problem in question through which aspects were identified that predominated in the idea that a person can have a high performance but is not productive because factors such as the work environment, the level of education acquired and the attitude of a secretary influence the time to perform activities correctly and efficiently.